Peran Guru AUD Dalam Menstimulasi Perkembangan Bahasa Anak di TK Ikhlasul ‘Amal Medan - Siahaan, Hasnah; Muhammad, Arifin; Mahfudza, Amalia; Afni, Fitria Nurafni; Zr, Jamilah; Lestari, Sekar Ayu (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study aims to determine the role of the aud teacher in stimulating children's language development in Kindergarten Ikhlasul 'Amal Medan. In this study, the authors found that in Ra, the teacher's role in teaching focuses on children's "Calistung", the teacher uses reading books, or fairy tale books to teach children to read and write in teaching children. This research uses a type of qualitative research with a descriptive approach. The approach taken is literary in nature and is included in the category of approaches used in library research. The method given by the teacher in learning is a system of writing, reading, spelling. Furthermore, the children will be given the task to improve their writing and reading. The teacher at Ra also differentiates children's language development through their age. Keywords: Early childhood, child language development